Assessing the distribution, composition and potential human health implications of metal-bearing particulate matter in the Saldanha Bay Municipality - Ebrahim, Laylaa (Department of Chemical Engineering, 2025)
Air pollution through the emission of particulate matter (PM) can have a significant impact on the surrounding environment. PM2.5 and PM10 is of particular concern as it is known to reduce the quality of air and can cause adverse health effects on surrounding communities. The overarching aim of this paper was to assess the particulate matter (PM) concentration and composition in the Saldanha Bay Municipality, and based on these results, to assess the potential sources and potential health implications of these emissions. To address the aim and objectives, this paper includes the selection of the sampling/monitoring sites and the collection of background data. The processing and interpretation of the primary data from PM monitoring and sample collection provides a view in understanding the nature and patterns of PM pollution and the potential sources and health risks associated with these emissions. PM concentrations were obtained from PurpleAir Particulate Sensors and physical PM samples were collected from gravimetric samplers, dust fallout buckets and BSNEs for elemental and mineral analysis. Pollution roses and polar plots were constructed to assist in determining the potential origins and sources of emission in the municipality. Minerals such as hematite, lead, arsenic, thorium and uranium, to mention a few, were found in the samples and could potentially result in negative health implications to those in surrounding communities. It is envisaged that the results from this paper can be used to inform future studies by providing information on the potential components of concern and their possible sources.